2022
DOI: 10.1007/s00415-022-11451-x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis exploring the efficacy of mindfulness-based interventions on quality of life in people with multiple sclerosis

Abstract: Background Quality of life (QoL) is commonly impaired among people with multiple sclerosis (PwMS). The aim of this study was to evaluate via meta-analysis the efficacy of Mindfulness-based interventions (MBIs) for improving QoL in PwMS. Methods Eligible randomized controlled trials (RCTs) were identified via searching six major electronic databases (MEDLINE, EMBASE, CINAHL, Cochrane Central Register of Controlled Trials, AMED, and PsycINFO) in April 2022. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 73 publications
0
3
0
1
Order By: Relevance
“…This study shows that MBCT reduced a wide variety of self-reported psychological symptoms directly following treatment completion, including depressive symptoms, fatigue and brooding, of which the latter is a central target of mindfulness interventions. These small-to-moderate effects are in accordance with previous mindfulness-based studies [13], but we extend these findings by revealing the feasibility and effectiveness of MBCT within a sample that encompasses cognitively impaired patients. Patients with cognitive impairments are generally not included in previous studies [13], whereas our sample included 57% of these patients.…”
Section: Discussionsupporting
confidence: 91%
“…This study shows that MBCT reduced a wide variety of self-reported psychological symptoms directly following treatment completion, including depressive symptoms, fatigue and brooding, of which the latter is a central target of mindfulness interventions. These small-to-moderate effects are in accordance with previous mindfulness-based studies [13], but we extend these findings by revealing the feasibility and effectiveness of MBCT within a sample that encompasses cognitively impaired patients. Patients with cognitive impairments are generally not included in previous studies [13], whereas our sample included 57% of these patients.…”
Section: Discussionsupporting
confidence: 91%
“…Firstly, among healthy participants, there is a moderate correlation between HRQoL and mindfulness, indicating that individuals with higher levels of mindfulness tend to report better overall well-being. This aligns with previous research demonstrating the positive impact of mindfulness on various aspects of health and quality of life [36][37][38]. Similarly, the low correlation between HRQoL and adherence to the Mediterranean Diet suggests that while diet may influence certain dimensions of well-being, its association with overall quality of life may be less pronounced.…”
Section: Discussionsupporting
confidence: 89%
“…Já as intervenções baseadas em mindfulness, ou terapias de mindfulness, auxiliam na saúde mental dos pacientes, principalmente no quesito depressão, uma vez que é trabalhado e desenvolvido nos pacientes portadores de EM a aceitação, autoeficácia e autocompaixão (SIMPSON et al, 2023).…”
Section: Discussionunclassified